TINDAK PIDANA UMUM “ANALISIS KASUS TINDAK PIDANA PENGANIAYAAN BERAT YANG DI RENCANAKAN DI KOTA KUPANG” - Samara, Finsensius; Esparance Fallo, Maria Cornelia; Adelbertha Hoar, Ayuni; Talele Mudapue, Petrus; Nikolas Tadji, Felisiano; Rana, Yeremias; Beda Baon, Markus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The planned crime of serious persecution is a form of serious crime that has a significant impact on victims and society. This study aims to analyze the elements of planned serious persecution crimes, the legal process applied, and juridical and non-juridical considerations in case decision-making. The analyzed cases involved individuals who committed persecution with deliberate intention and planning, resulting in serious injuries to the victim. The results of the analysis showed that the act met all the elements of the crime of severe persecution, including the existence of malicious intent, planning, and adverse consequences. The legal process carried out includes a comprehensive investigation and investigation, as well as the judge's consideration of juridical and non-juridical aspects to achieve justice. The findings of this study provide a better understanding of the application of criminal law in cases of planned aggravated persecution and the importance of fair and balanced law enforcement.